Palyno-morphological characterization of selected allergenic taxa of family Poaceae from Islamabad-Pakistan using microscopic techniques - Ullah, Izhar; Ahmad, Mushtaq; Jabeen, Asma; Yusuf, M. Osman; Arfan, Muhammad; Kilic, Omer; Usma, Anwer (Wiley, 2021)
Statistics around the world show an increased risk of high allergies associated with plants. The role of allergenic pollen is now well known. The most serious allergenic diseases are asthma and rhinitis, which affect 5-30% of the population of industrialized countries. This work focuses on the exploration of allergenic grass species of Islamabad, Pakistan and use microscopic techniques to correctly identify them. This study contains 11 species of grasses which showed variations in pollen morphological features. The dominant pollen shape was prolate, prolate-spheroidal and sub oblate. The largest polar diameter was calculated for Echinochloa crus-galli (56.00 mu m) while the largest equatorial diameter was found in Cenchrus ciliaris (45.00 mu m). Exine ornamentation varied from Gemmate-verrucate, Scabrate-reugulate, Verrucate-reticulate, Gemmate-Scabrate, Fine-Gemmate, Gemmate-rugulate, Gemmate-reticulate, Gemmate-scabrate, Scabrate-verrucate, and Scabrate. Maximum exine thickness was found in Eleusine indica (4.90 mu m) while in C. ciliaris (1.50 mu m) the minimum thickness of exine was measured. In E. crus-galli (1.54 mu m), the largest P to E value was measured and the smallest value was noticed in Setaria verticillata (0.86 mu m). The study was performed with an aim to identify the allergenic plant species in Islamabad-Pakistan using pollen morphological studies. This study provides significant information, to arrange the pollen types within their defined classes and to discuss various pollen features for developing an allergenic pollen atlas.
Keywords: allergenic plants; LM; Poaceae; pollen morphology; SEM